Comparative Genomics Identifies a Novel Conserved Protein, HpaT, in Proteobacterial Type III Secretion Systems that Do Not Possess the Putative Translocon Protein HrpF - Pesce, Céline; Jacobs, Jonathan M.; Berthelot, Edwige; Perret, Marion; Vancheva, Taca; Bragard, Claude; Koebnik, Ralf (Frontiers in Microbiology, 2017)
Xanthomonas translucens is the causal agent of bacterial leaf streak, the most common bacterial disease of wheat and barley. To cause disease, most xanthomonads depend on a highly conserved type III secretion system, which translocates type III effectors into host plant cells. Mutagenesis of the conserved type III secretion gene hrcT confirmed that the X. translucens type III secretion system is required to cause disease on the host plant barley and to trigger a non-host hypersensitive response in pepper leaves. Type III effectors are delivered to the host cell by a surface appendage, the hollow Hrp pilus, and a translocon protein complex that inserts into the plant cell plasma membrane. Homologs of the Xanthomonas HrpF protein, including PopF from Ralstonia solanacearum and NolX from rhizobia, are thought to act as a translocon protein. Comparative genomics revealed that X. translucens strains harbor a noncanonical hrp gene cluster, which rather shares features with type III secretion systems from Ralstonia solanacearum, Paraburkholderia andropogonis, Collimonas fungivorans and Uliginosibacterium gangwonense than other Xanthomonas spp. Surprisingly, none of these bacteria, except R. solanacearum, encode a homolog of the HrpF translocon. Here, we aimed at identifying a candidate translocon from X. translucens. Notably, genomes from strains that lacked hrpF/popF/nolX instead encode another gene, called hpaT, adjacent to and co-regulated with the type III secretion system gene cluster. An insertional mutant in the X. translucens hpaT gene, which is the first gene of a two-gene operon, hpaT-hpaH, was non-pathogenic on barley and did not cause the hypersensitive response or programmed cell death in non-host pepper similar to the hrcT mutant. The hpaT mutant phenotypes were partially complemented by either hpaT or the downstream gene, hpaH, which has been described as a facilitator of translocation in Xanthomonas oryzae. Interestingly, the hpaT mutant was also complemented by the hrpF gene form Xanthomonas euvesicatoria. These findings reveal that both HpaT and HpaH contribute to the injection of type III effectors into plant cells.